2003
DOI: 10.3139/217.1730
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Non-Newtonian Behaviour on the Processing Characteristics of Wall-slipping Materials

Abstract: So far it has been assumed that when describing the flow process in single-screw extruder, the melt will be wall-adhering. Using certain process conditions, however, some materials such as PVCs, high-molecular PEs, elastomers, polymer suspensions, ceramic materials and food products become wall-slipping [1 to 4].During simulation of the flow process using the Finite Element Method (FEM), the boundary condition of “wall-adhering” was substituted for “wall-slipping”. The numeric results refer to one-dimensional,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 1 publication
1
6
0
Order By: Relevance
“…This stronger bonding to the steel surface usually results in wall adherence. The measured rheological data revealed wall slip even at low wall shear stress values. Other authors , who observed different slip mechanisms reported the first appearance of wall slip after exceeding a critical wall shear stress value. Generally, the experimentally determined slip velocity data correlate well with the dependencies predicted with the presented slip model in this paper, which considers a lubricating film between the die wall and the polymer melt. The experimentally obtained slip velocity increases with rising wall shear stress. The presented slip model predicts a power law dependency on wall shear stress.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…This stronger bonding to the steel surface usually results in wall adherence. The measured rheological data revealed wall slip even at low wall shear stress values. Other authors , who observed different slip mechanisms reported the first appearance of wall slip after exceeding a critical wall shear stress value. Generally, the experimentally determined slip velocity data correlate well with the dependencies predicted with the presented slip model in this paper, which considers a lubricating film between the die wall and the polymer melt. The experimentally obtained slip velocity increases with rising wall shear stress. The presented slip model predicts a power law dependency on wall shear stress.…”
Section: Resultssupporting
confidence: 85%
“…Typical polymers which are known to slip at the wall when a critical wall shear stress is exceeded are polyvinyl chloride (PVC), high molecular weight polyethylene (PE), high density polyethylene (HDPE), linear low density polyethylene (LDPE), branched polypropylene (PP), polybutadiene, polyisobutylene (PIB), polylactides (PLA), fluoropolymers, highly filled polymers and elastomers .…”
Section: Introductionmentioning
confidence: 99%
“…Kalyon et al [241] as well as Malik et al [183] studied numerically co-rotating twin-screw extrusion with wall slippage at the barrel and screws. Potente and his co-workers, e.g., [236,[242][243][244][245][246] performed very extensive studies on modeling single-screw extrusion with slip effects, both analytically and numerically, by calculating the pressure/throughput and drive power behavior, as well as the melt temperature development in single-screw extrusion of wall-slipping polymers. Several studies were performed on modeling the flow of wall slipping polymers in the dies, e.g., by Ferras et al [247], Hatzikiriakos and Mitsoulis [248], and Gupta [249].…”
Section: Computer Models Of Extrusionmentioning
confidence: 99%
“…It is widely known that, under particular conditions, some materials, such as filled polymers, elastomers, and polyvinyl chloride, exhibit wall slippage—that is, a relative velocity between the fluid velocity at the wall and the wall velocity. Numerous studies have used a variety of slip conditions to account for wall slippage [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ].…”
Section: Modeling Fundamentalsmentioning
confidence: 99%